2006
DOI: 10.1007/s10633-006-9017-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spatial frequency of stimulus on focal macular ERGs in monkeys

Abstract: The OPs of the photopic macular ERGs are affected by the spatial frequency of the stimulus and are reduced by TTX, consistent with their being generated by inner retinal neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous studies have used various ERG techniques to investigate the SF effect on retinal response [ 51 54 ]. Yamada and colleagues [ 54 ] applied focal macular ERG and found that the oscillatory potentials, which reflect the inner retina activity, decreased with increasing SF, and our findings are consistent with theirs. It has long been suggested that the retina has different channels which are selectively sensitive (tuned) to particular ranges of SF [ 55 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used various ERG techniques to investigate the SF effect on retinal response [ 51 54 ]. Yamada and colleagues [ 54 ] applied focal macular ERG and found that the oscillatory potentials, which reflect the inner retina activity, decreased with increasing SF, and our findings are consistent with theirs. It has long been suggested that the retina has different channels which are selectively sensitive (tuned) to particular ranges of SF [ 55 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are essentially three ways to deliver a stimulus to a specific area of the retina under fundus observation; through a fundus camera as is done with the Miyake system [ 2 7 ], through a slit-lamp microscope[ 8 , 9 ], or through a direct ophthalmoscope [ 10 ]. All of these methods are non-invasive and easily performed in the clinic, and several investigators have evaluated the macular function in different macular diseases with one of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…(Miyake 1998 Their recording system for fmERGs was based on a fundus camera into which a focal stimulus system was integrated. Another system to record fmERGs was developed by Matsumoto et al (Choshi et al, 2003;Yamada et al, 2006) Their system is based on a slit-lamp microscope, and both the focal stimulus and fundus observation systems were integrated into the slit-lamp. With both systems, the examiner records the ERGs while monitoring the stimulus on the fundus either by an infrared television fundus camera or a slit-lamp-mounted infrared CCD camera.…”
mentioning
confidence: 99%